Nilai -Nilai Hak Asasi Manusia Dalam Buku Ajar Pendidikan Agama Islam di Sekolah Menengah Atas Daerah Istimewa Yogyakarta - Fahrurrozi - (Millah: Journal of Religious Studies, 2005)
This research aims to know the characteristic appears in the textbook of Islamic education and to describe the development of integration of human right values into text book of Islamic education in Senior high school Yogyakarta. The textbook published by Department of Religious Affairs and information from the teachers are the primary data for this research. Based on the data accepted, this research concludes two main ideas: First, the textbook has not being reflected the vision of appreciation toward human rights. Second, based on this inclination, the content of textbook needs to be revised until it really contains human right values.